When Words Offend: A Study of Indonesian Political Speech - Loeis, Jhonson; Lubis, Heri Setiawan; Fadillah, Teuku Muhammad Raihan; Rangkuti, Rahmadsyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores how political speech in Indonesia functions as a catalyst for public anger by violating cultural norms of respectful communication, or tata bicara. Using Critical Discourse Analysis (CDA), it examines five controversial statements made by public officials between 2023 and 2024, analyzing how linguistic choices—such as tone, vocabulary, and framing—trigger emotional backlash. Data were collected from televised interviews, press conferences, and online news reports that documented these public statements. The selected data represent speech events that sparked significant public debate and reactions on social media. Findings reveal recurring patterns of superiority language, blame-shifting, and a lack of empathy, all of which undermine expectations of humility and politeness in political discourse. Drawing on Politeness Theory, Speech Act Theory, and sociolinguistic insights, the study argues that public anger is not just a reaction to policy, but to the emotional and moral dissonance created by disrespectful speech. In the Indonesian context, language is deeply tied to social harmony; when violated, it becomes a site of moral contestation. The research highlights the urgent need for empathetic authority in political communication.